2019
DOI: 10.1002/jmv.25411
|View full text |Cite
|
Sign up to set email alerts
|

Non‐F HBV/HDV‐3 coinfection is associated with severe liver disease in Western Brazilian Amazon

Abstract: The clinical outcome of hepatitis B virus (HBV) infection may be related to host and viral genetic factors, as well as to the type of infection (monoinfection and coinfection). To analyze the distribution/combination of HBV/hepatitis D virus (HDV) genotypes and the associated clinical characteristics, 409 serum samples from patients with chronic HBV (94 of them coinfected by HDV) followed at the Viral Hepatitis Referral Center of Rio Branco, Brazil were enrolled. HBV DNA and HDV RNA were amplified, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
1
16
0
2
Order By: Relevance
“…In Venezuela, both HDV I and HDV III were isolated from patients with HDV infection (85). In Brazilian Amazon, the most detected HDV genotype was HDV III (17)(18)(19)(20)(21)(22)(23)(24) while in Minas Gerais state, south of Brazil, and outside of Amazon basin, the only isolated HDV genotype was HDV I (25). These results confirm Amazon as the origin of HDV III.…”
Section: Discussionsupporting
confidence: 57%
“…In Venezuela, both HDV I and HDV III were isolated from patients with HDV infection (85). In Brazilian Amazon, the most detected HDV genotype was HDV III (17)(18)(19)(20)(21)(22)(23)(24) while in Minas Gerais state, south of Brazil, and outside of Amazon basin, the only isolated HDV genotype was HDV I (25). These results confirm Amazon as the origin of HDV III.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, we chose to use a recombinant plasmid as the assay quanti cation standard that presented a consensus sequence of the 8 HDV genotypes, bearing in mind that the Amazon region presents a predominance of Genotype 3 10,27,28 , and the standard established by the WHO for HDV quanti cation is derived from genotype 1 29 . Likewise, the primers used in the standardization were designed in order to detect a conserved region for the 8 virus genotypes, guaranteeing the sensitivity and speci city of the test.…”
Section: Discussionmentioning
confidence: 99%
“…The same issue of late diagnosis of HDV infection and delays seeking medical attention has been reported in other endemic regions of the world. Melo Da Silva et al reported that up to 10% of patients with HDV infection in the western Brazilian Amazon had advanced liver disease when they first sought medical attention 24 . This is presumably due to widely adopted practice of testing for HDV only in HBsAg‐positive patients with advanced liver disease that results in the missing the diagnosis in the milder forms of the disease.…”
Section: Discussionmentioning
confidence: 99%